Understanding gratitude: Starting from its conceptualisations. - Yeo, Yet Phing (Universiti Sains Malaysia, 2014)
The study of gratitude has been started since decades ago. This single word “gratitude” has been defined in many different ways. Apparently, this is rather confusing for new researchers to understand gratitude from diverse perspectives.